ANALISIS DAMPAK LINGKUNGAN PERKEMBANGAN INDUSTRI TERHADAP KESEHATAN MASYARAKAT DI KABUPATEN BOYOLALI - Heru Nur Alamsyah; Yosep Natan Nitit; Muryanto; Akhyari; Silitonga, Frangky; Sermatutar Luhur Imam Seto; Sermadatar Dimas Widhi Nugraha (PPM Sdirjianbang Akademi Militer, 2024)
Public health as the science and art of preventing disease, prolonging life, and improving the quality of life by making organizational efforts and providing informed choices to communities, organizations, communications, and individuals. The goal of national development is the full human development of Indonesia. Namely Indonesian human development both physically and mentally, human development is basically an effort to humanize humans again. Keyongan village, Nogosari Sub-District, Boyolali regency as an area for medium-sized industries in the form of Agriculture, paper, wood industry, publishing, printing, apparel and similar industries. This is in accordance with Rpjm Kab. Boyolali since 2010 now 2024 which launched the program “Pro Invenstment